1987
DOI: 10.1002/j.1460-2075.1987.tb02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter and enhancer elements containing a conserved sequence motif are recognized by nuclear factor III, a protein stimulating adenovirus DNA replication.

Abstract: Nuclear factor HI (NFI) is a protein from HeLa cells that stimulates the initiation of adenovirus type 2 (Ad2) DNA replication by binding to a specific nucleotide sequence in the orign, adjacent to the nuclear factor I recognition site. DNA sequences sharing a high degree of homology to the NFm binding site in Ad2 were found in a number of transcription regulatory elements, all containing the octanucleotide sequence ATGCAAAT. We have analysed the interaction between NF[II and the octamer-containing sequences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 48 publications
4
61
1
Order By: Relevance
“…proximal upstream region was searched for putative cw-regulatory sequences: Octamer-1 and -4 (Oct-1 and Oct-4) binding sites [11] and a ssARS-T binding site [12] were found (Fig. 2).…”
Section: Determination Of the Nucleic Sequences Flanking The Ktx 2 Genementioning
confidence: 99%
“…proximal upstream region was searched for putative cw-regulatory sequences: Octamer-1 and -4 (Oct-1 and Oct-4) binding sites [11] and a ssARS-T binding site [12] were found (Fig. 2).…”
Section: Determination Of the Nucleic Sequences Flanking The Ktx 2 Genementioning
confidence: 99%
“…EMSA binding conditions were determined as described [17]. Briefly, binding reactions were performed by mixing DNA probes, ds competitor DNA and binding buffer [20 mM Hepes\KOH (pH 7.6)\1 mM MgCl # \75 mM KCl\1 µg of poly(dI-dC) (Pharmacia, Uppsala, Sweden)\1 mM dithiothreitol\0.018 % Nonidet P40], after which protein extract was added.…”
Section: Emsamentioning
confidence: 99%
“…DNase I footprinting reactions were performed as described previously [17]. The probe for DNase I footprinting contained an EcoRI\SalI P3 fragment from k290 to j134 labelled in the upper strand.…”
Section: Dnase I Footprintingmentioning
confidence: 99%
“…Inspection of nucleotide sequences of ARSs reveals that there are multiple MCE-like elements in certain ARSs (V. Chang, unpubl.). Many examples of site-specific DNA-binding proteins playing dual roles in transcriptional activation and replication initiation in eukaryotes have been described (Dean et al 1987;Jones et al 1987;Mecas and Studgen 1987;Pruijn et al 1987;Stenlund et al 1987;O'Neill and Kelly 1988). A recent report by Santoro et al (1988) convincingly showed that a family of CCAAT-box binding proteins serves both as promoter-selective transcription activators and as initiation factors for DNA replication in mammalian in vitro systems.…”
Section: Possible Role In Dna Replicationmentioning
confidence: 99%